Simulating the urban growth of a predominantly informal Ghanaian city-region with a cellular automata model: Implications for urban planning and policy. (April 2019) - Agyemang, Felix S.K.; Silva, Elisabete
Abstract: This paper explores two main objectives: first, simulates the urban growth of a Ghanaian city-region with a CA model, drawing implications for urban planning and policy; and, second, explores the sensitivity of CA models to predominantly informal and un-regulated urban growth trajectories. CA model, SLEUTH, is calibrated for Accra city-region, and the results are triangulated with, knowledge from key local stakeholders, and findings from existing studies. The study finds that, compared with cases around the world, urban expansion in Accra city-region is highly spontaneous, rapid and unguided; and new developments fast turn into urban growth nuclei. These have reflected in a sharp rise of the city-region's land under built-up from less than 4 percent in 1990 to about 15 percent in 2015, and it is further simulated to reach around 33 percent by 2040, posing serious challenges to urban management, and threats to sustainable development. The Ghanaian planning system faces the option of swiftly addressing emerging unguided developments or wait and be confronted with a more daunting challenge of managing multiple informal growth nuclei. We also find that the applied CA model is sensitive to the highly informal urban growth trajectory of the city-region. Going forward, it is imperative for policy makers to build a more proactive, stronger and functional planning system; treat every single informal development as a potential threat to urban sustainability; and target pressure areas of expansion. The model's sensitivity to the growth trajectory of Accra city-region suggests that CA models could function as decision support tools even in overwhelmingly informal and less regulated contexts like Ghana. Highlights: Simulates the urban growth of a predominantly informal and rapidly urbanizing Ghanaian city-region. Explores the sensitivity of Cellular Automata (CA) model to informal and un-regulated urban growth trajectories. Simulated urban expansion poses serious threats to sustainable development and challenges to urban planning and policy. CA models offer valuable planning decision support, even in contexts where urban growth is overwhelmingly informal.